Mechanical Anastomotic Coupling Device versus Hand-sewn Venous Anastomosis in Head and Neck Reconstruction—An Analysis of 1694 Venous Anastomoses - Rajan Arora; Kripa Shanker Mishra; Hemant T. Bhoye; Ajay Kumar Dewan; Ravi K. Singh; Ravikiran Naalla (Indian Journal of Plastic Surgery)
Background There is a steep learning curve to attain a consistently good result in microvascular surgery. The venous anastomosis is a critical step in free-tissue transfer. The margin of error is less and the outcome depends on the surgeon’s skill and technique. Mechanical anastomotic coupling device (MACD) has been proven to be an effective alternative to hand-sewn (HS) technique for venous anastomosis, as it requires lesser skill. However, its feasibility of application in emerging economy countries is yet to be established. Material and Method We retrospectively analyzed the data of patients who underwent free-tissue transfer for head and neck reconstruction between July 2015 and October 2020. Based on the technique used for the venous anastomosis, the patients were divided into an HS technique and MACD group. Patient characteristics and outcomes were measured. Result A total of 1694 venous anastomoses were performed during the study period. There were 966 patients in the HS technique group and 719 in the MACD group. There was no statistically significant difference between the two groups in terms of age, sex, prior radiotherapy, prior surgery, and comorbidities. Venous thrombosis was noted in 62 (6.4%) patients in the HS technique group and 7 (0.97%) in the MACD group (p = 0.000). The mean time taken for venous anastomosis in the HS group was 17 ± 4 minutes, and in the MACD group, it was 5 ± 2 minutes (p = 0.0001). Twenty-five (2.56%) patients in the HS group and 4 (0.55%) patients in MACD group had flap loss (p = 0.001). Conclusion MACD is an effective alternative for HS technique for venous anastomosis. There is a significant reduction in anastomosis time, flap loss, and return to operation theater due to venous thrombosis. MACD reduces the surgeon’s strain, especially in a high-volume center. Prospective randomized studies including economic analysis are required to prove the cost-effectiveness of coupler devices.